HUBUNGAN KEPEMIMPINAN DAN LINGKUNGAN KERJA DENGAN KEPUASAN KERJA GURU - Nurhasan Nurhasan (JTPPm (Jurnal Teknologi Pendidikan dan Pembelajaran) : Edutech and Intructional Research Journal, 2020)
The purpose of this study was to determine the relationship of leadership and work environment together with teacher job satisfaction at the Kartika Jaya Foundation Branch XVIII Jayakarta. This type of research is a quantitative field research with a correlational approach.  This  research  was conducted  at the  Yayasan  Kartika  Jaya Branch School XVIII Jayakarta. The population in this study was the teacher of Kartika Jaya Foundation Branch XVIII Jayakarta with a total sample of 88 teachers. The results showed that: 1) The correlation analysis results between leadership and teacher job satisfaction obtained Pearson Correlation value of (rcount) 0.618. with a Significance value of 0,000. With these results, it can be concluded that there is a relationship between  leadership  and  teacher  job  satisfaction;  2)  The  results  of  the  correlation analysis between work environment and teacher job satisfaction obtained Pearson Correlation value of 0.522, with a Significance value of 0,000. Then it can be concluded that there is a relationship between the work environment with teacher job satisfaction; 3) Analysis of multiple correlations obtained correlation coefficients are meaningful (significant). This is because the Fcount value obtained is 30.517, while with a df of 85.2 and a significance level of 0.05, the Ftable value of 3.104 is obtained. After comparing it turns out that the value of Fcount> F table (30.517> 3.104). From the results of the hypothesis test, it can be stated that the hypothesis which states that there is a positive and significant relationship between leadership and work environment together with teacher job satisfaction at the Kartika Jaya Foundation, Jayakarta Branch XVIII, is proven  to  be  true.  The  magnitude  of  the  contribution  of  leadership  and  work environment contributes to teacher job satisfaction, it can be seen from the value of R Square of 0.418 (41.8%). this means that jointly the leadership and work environment contributed 41.8% to the teacher job satisfaction at the Kartika Jaya. Keywords: Leadership, Work Environment, Teacher Job Satisfaction